The acceleration of reproductive aging in Nrg1flox/flox;Cyp19‐Cre female mice. Issue 6 (31st August 2017) - Umehara, Takashi; Kawai, Tomoko; Kawashima, Ikko; Tanaka, Katsuhiro; Okuda, Satoshi; Kitasaka, Hiroya; Richards, JoAnne S.; Shimada, Masayuki
Summary: Irregular menstrual cycles, reduced responses to exogenous hormonal treatments, and altered endocrine profiles (high FSH/high LH/low AMH) are observed in women with increasing age before menopause. In this study, because the granulosa cell‐specific Nrg1 knockout mice (gc Nrg1 KO) presented ovarian and endocrine phenotypes similar to older women, we sought to understand the mechanisms of ovarian aging and to develop a new strategy for improving fertility in older women prior to menopause. In the ovary of 6‐month‐old gc Nrg1 KO mice, follicular development was blocked in bilayer secondary follicles and heterogeneous cells accumulated in ovarian stroma. The heterogeneous cells in ovarian stroma were distinguished as two different types: (i) the LH receptor‐positive endocrine cells and (ii) actin‐rich fibrotic cells expressing collagen. Both the endocrine and fibrotic cells disappeared following long‐term treatment with a GnRH antagonist, indicating that the high levels of serum LH induced the survival of both cell types and the abnormal endocrine profile to reduce fertility. Moreover, follicular development to the antral stages was observed with reduced LH and the disappearance of the abnormal stromal cells. Mice treated with the GnRH antagonist regained normal, recurrent estrous cycles and continuously delivered pups for at least for 3 months. We conclude that endocrine and matrix alternations occur within the ovarian stroma with increasing age and that abolishing these alternations resets the cyclical release of LH. Thus, GnRH antagonist treatments might provide a new, noninvasive strategy for improving fertility in a subset of aging women before menopause.